Early Career Members at the Lung Science Conference and the Sleep and Breathing Conference 2019. Issue 3 (September 2019) - Almendros, Isaac; El-Merhie, Natalia; Jha, Akhilesh; Keir, Holly R.; Lykouras, Dimosthenis; Mahmutovic Persson, Irma; Ubags, Niki D.; Bartel, Sabine
The European Respiratory Society (ERS) Lung Science Conference (LSC) is the basic science conference of the ERS and it takes place every March in Estoril, Portugal. It is important to note that, particularly at this conference, there is a lot of emphasis on the inclusion and development of Early Career Members. For example, each session is chaired by one Early Career Member together with a more senior scientist; there are 40 travel bursaries to enable abstract authors to attend the conference; there is a mentorship lunch session; and every year the Early Career Member Committee (ECMC) organises a specifically dedicated Early Career Member career development session on the Saturday afternoon. Thus, there are many reasons for Early Career Members to attend this conference but, for those who could not attend, we will describe here the scientific highlights of the LSC 2019 on the topic "Mechanisms of acute exacerbation of respiratory disease". The Lung Science Conference and the Sleep and Breathing Conference 2019 brought together leading experts in the field to discuss the latest cutting-edge science, as well as various career development opportunities for early career members http://bit.ly/2XNX6V6